Full‐Color and White Circularly Polarized Luminescence of Hydrogen‐Bonded Ionic Organic Microcrystals - Li, Zhong‐Qiu; Gong, Zhong‐Liang; Shao, Jiang‐Yang; Yao, Jiannian; Zhong, Yu‐Wu (Angewandte Chemie International Edition, 2021)
A simple and general method is presented herein for the in situ preparations of circularly polarized luminescence (CPL)‐active microcrystals with a large luminescence dissymmetry factor glum, high fluorescence quantum efficiency (ΦFL), wide emission color tenability, and well‐ordered morphology. The reactions of pyridine‐containing achiral molecules 1–7 with chiral camphor sulfonic acid ((±)‐CSA) gave crystalline microplates formed by hydrogen bonding interactions between the protonated pyridinium units and the sulfonic anions. The chiral information of CSA are effectively transferred to the microcrystals by hydrogen bonding to afford full‐color CPL from deep‐blue to red with glum in the order of 10−2 and ΦFL up to 80 %. Moreover, organic microcrystals with high‐performance white CPL (ΦFL=46 %; |glum|=0.025) are achieved via the light‐harvesting energy transfer between blue and yellow emitters. As a result of the efficient hydrogen‐bonding‐mediated chirality transfer and light‐harvesting energy transfer, well‐ordered ionic microcrystals formed between pyridine‐containing achiral molecules and chiral camphor sulfonic acid display full‐color and homogeneously white circularly polarized luminescence (CPL) with ΦFL of up to 80 % and glum in the order of 10−2.